Cafestol extraction yield from different coffee brew mechanisms - Zhang, Chen; Linforth, Rob S.T.; Fisk, Ian D. (Elsevier, 2012)
The extraction yield of cafestol from roast and ground (R&G) coffee beans was evaluated using brews prepared by four brewing mechanisms (boiled, Turkish, French Press and Mocha Pot). The cafestol content of the R&G coffee and the resulting brews was measured and extraction yield calculated. The R&G coffee had an average cafestol content of 603 mg/100 g R&G coffee with a slight reduction at higher roast intensities. In the brews, preparation method had an impact on cafestol concentration with French, Turkish and boiled preparation methods producing the highest cafestol concentrations. The extraction yield of cafestol was shown to be dependent on the brew mechanism and roasting time, with the lightest roast coffee prepared by French press or boiled preparations having the highest cafestol extraction yield (6.5% and 5.84%) and dark roast Mocha and Turkish preparations had the lowest extraction yields of 2.42% and 2.88% respectively.